Comparison of the influence of different rehabilitation programmes on clinical, spirometric and spiroergometric parameters in patients with multiple sclerosis - Rasova, K; Havrdova, E; Brandejsky, P; Zálisová, M; Foubikova, B; Martinkova, P (Multiple sclerosis (Houndmills, Basingstoke, England), 2006)
PURPOSE: The aim of this study was to compare the effect of four different programmes on spiroergometric, spirometric and clinical parameters in multiple sclerosis (MS) patients. METHODS: One hundred and twelve MS patients were divided into four groups. The first group underwent neurophysiologically based physiotherapy, the second aerobic training, the third combined therapy (neurophysiologically based physiotherapy and aerobic training) and the fourth did not change any habits. Seventeen patients did not finish the study. Patients were examined on impairment (Expanded Disability Status Scale), disability (Barthel Index), handicap (Environment Status Scale), quality of life (Multiple Sclerosis Quality of Life), fatigue (Modified Fatigue Impact Scale), depression (Beck Depression Inventory Score), respiratory function (spirometric parameters on spirometry) and physical fitness (spiroergometric parameters on a bicycle ergometer). RESULTS: The patients who participated in one of our training programmes showed a significant improvement of the examined parameters in comparison to those who did not change their present habits. Each of the four training programmes had a different impact on the parameters, which means that each of them had a different effect. The neurophysiologically based physiotherapy had the greatest impact on impairment, and the aerobic training on spirometric and spiroergometric parameters. All methods (the neurophysiologically based physiotherapy, the aerobic training and the combined programme) had an impact on fatigue.
Keywords: kvalita života; zátěžový test; roztroušená skleróza; terapie cvičením; Persons with Disabilities; Multiple Sclerosis; techniky fyzikální terapie; lidé; spirometrie; Physical Therapy Modalities; postižení; Exercise Therapy; Quality of Life; Humans; Exercise Test; Spirometry